PARTISIPASI MASYARAKAT DALAM PENGAWASAN PEMILU DI DESA NGUJUNG, KECAMATAN MAOSPATI, KABUPATEN MAGETAN - Taufiq Yuli Purnama; Sigit Sapto Nugroho; Subadi; Mudji Rahardjo (Universitas Merdeka Madiun, 2023)
The purpose of writing this journal is to achieve balance and realize a democratic state based on Pancasila. Bawaslu Regulation Regulation of the General Election Supervisory Agency Number 21 of 2018 concerning Supervision of the Implementation of General Elections which regulates forms of public participation. The method used in the implementation of community service uses legal and practical counseling methods. In this socialization, it is a form of community participation in supervising general elections. Community service activities are carried out for the community and village officials regarding the form of community participation in supervising general elections. The results of the implementation of community service are the importance of the participation of elements of the community in this oversight function will affect the realization of strengthening the authority of Bawaslu in the implementation of elections in Indonesia where this also has an influence on the law enforcement of election organizers in Indonesia, in this case is community participation, the benchmark for community participation here can be measured from the existence of community participation in supervising the implementation of elections, especially in Ngujung Village to achieve balance and realize a democratic state based on Pancasila.